Proverbs & Parables: God's wisdom for living - Brestin, Dee; (1944-...) (U.S.A., 2002)
This study guide links the truths of the proverbs and the parables and applies them to contemporary living. It offers penetrating questions, a flexible format for groups and helpful leader's notes.
Keywords: Religion -- Biblical Studies -- Old Testament